PENERAPAN MODEL ENTERPRISE ARCHITECTURE UNTUK MENENTUKAN SISTEM INFORMASI DI SEKOLAH MENEGAH ATAS MENGGUNAKAN EAP (STUDI KASUS : SMA NEGERI I SUKOHARJO) - Yasir Sipung (IIB Darmajaya, 2016)
Enterprise Architecture Planning is a method used to build an information architecture. Literally Enterprise Architecture Planning or EAP is a method of data quality planning approach that is oriented to business needs and how the implementation of the architecture is done in such a way in an effort to support the business wheel rotation and the achievement of mission information systems and organizations. Basically EAP is not designing the business and its architecture, but it defines the business needs and architecture. In EAP, architecture describes the data, applications and technologies needed to support the organization's business. SMA Negeri I Sukoharjo, as one of the providers of secondary education, also did not escape the need to define business needs and information architecture so that the direction of organizational development policy strategy can be well planned. this research is expected to SMP Negeri 1 Sukoharjo can have a good blueprint architectur enterprise and can be used as a proposal material to develop the information system, that is by building Enterprise Architectur Planning by using Zachman Framework which will produce a roadmap implementation of information system that is structured. Keywords: Enterprise Architecture Planning, Zachman Framework, system, and roadmap.